2010
DOI: 10.1038/nrc2773
|View full text |Cite
|
Sign up to set email alerts
|

Barrett's oesophagus and oesophageal adenocarcinoma: time for a new synthesis

Abstract: The public health importance of Barrett’s oesophagus lies in its association with oesophageal adenocarcinoma. The incidence of oesophageal adenocarcinoma has risen at an alarming rate over the past four decades in many regions of the Western world and there are indications that the incidence of this disease is on the rise in Asian populations where it has been rare. Much has been learned of host and environmental risk factors that affect the incidence of oesophageal adenocarcinoma and data indicate that patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
362
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(371 citation statements)
references
References 212 publications
(242 reference statements)
6
362
0
3
Order By: Relevance
“…6,7 When EAC recurs, the anatomic location of recurrence tends to be distant more often than in ESCC. 8,9 Whereas EAC incidence has dramatically increased since 1975 in the United States, ESCC incidence has dropped by half over the same time period.…”
Section: © 2010 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%
“…6,7 When EAC recurs, the anatomic location of recurrence tends to be distant more often than in ESCC. 8,9 Whereas EAC incidence has dramatically increased since 1975 in the United States, ESCC incidence has dropped by half over the same time period.…”
Section: © 2010 Mayo Foundation For Medical Education and Researchmentioning
confidence: 99%
“…Helicobacter pylori-induced chronic gastritis is a major cause of gastric intestinal metaplasia, from which intestinal-type adenocarcinoma arises (3). Likewise, replacement of the esophageal squamous epithelium by intestinal epithelium known as Barrett's esophagus substantially increases the risk of esophageal adenocarcinoma (2).…”
mentioning
confidence: 99%
“…From these observations, we concluded that aberrantly expressed CDX1 endowed gastric epithelial cells with an intestinal stem/progenitor-like phenotype. (1,2). Transgenic expression of Cdx1 has been reported to induce all of those epithelial cell lineages in the mouse stomach (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…EAC is becoming increasingly common and its incidence is associated with the prevalent precursor metaplastic condition Barrett's esophagus (BE), but with a low annual conversion rate of up to 1% (27). A common set of risk factors are described for BE and EAC, include gastroesophageal reflux disease (GERD), obesity, male gender, and smoking (28,29). The current endoscopybiopsy based diagnosis is invasive and costly, leading to an ineffective surveillance program.…”
mentioning
confidence: 99%